Proposed upgrading of Pendang Lake Resort for Pendang Lake Resort Sdn. Bhd. at Pekan Pendang, 06700, Pendang, Kedah Darul Aman / Nur Syazwani Ismail - Ismail, Nur Syazwani (Faculty of Architecture, Planning and Surveying, 2011)
The final project for student of Diploma Interior Design is a manisfestation towards the student's knowledge about the whole aspect on interior design that had been learned from basic until the final presentations on the proposed design. The project that had been chosen for the final project is proposed upgrading of Pendang Lake Resort for Pendang Lake Resort Sdn. Bhd. At Pekan Pendang, 06700, Pendang, Kedah . This proposed upgrading resort is to attract users, especially on tourist to experience Malaysian identity and culture.